GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 748 species occurrences available in GBIF matching the query: TaxonKey: Oena capensis capensis. The dataset includes 748 records from 32 constituent datasets: 1 records from University of Ghent - Zoology Museum - Vertebratacollectie. 18 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 2 records from Zoology (Museum of Evolution - Uppsala). 106 records from Field Museum of Natural History (Zoology) Bird Collection. 5 records from Museum Victoria provider for OZCAM. 21 records from Museum of Comparative Zoology, Harvard University. 1 records from CAS Ornithology (ORN). 8 records from NMNH occurrence DwC-A. 9 records from UMZC Zoological Specimens. 1 records from SBMNH Vertebrate Zoology. 29 records from LACM Vertebrate Collection. 84 records from Natural History Museum (London) Collection Specimens. 22 records from RBINS collections. 2 records from SDNHM Birds Collection. 22 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 32 records from ORN. 49 records from Naturalis Biodiversity Center (NL) - Aves. 49 records from Collection Aves (spirit preserved) SMF. 49 records from Collection Aves (bird skins) SMF. 121 records from AMNH Bird Collection. 5 records from CM Birds Collection. 15 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 2 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 3 records from rmca-albertine-rift-birds. 52 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Cowan Tetrapod Collection - Birds. 5 records from UMMZ Birds Collection. 13 records from IICT Colecção Zoológica. 5 records from MVZ Bird Collection (Arctos). 1 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 3 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). 11 records from South Australian Museum Australia provider for OZCAM.
Keywords: GBIF; biodiversity; species occurrences